IMPLEMENTASI SAK-EMKM BERBASIS MS. EXCEL TERHADAP LAPORAN KEUANGAN UMKM (STUDI KASUS PADA PETANI TOGE DI PULAU BINTAN – KEPULAUAN RIAU) - Hendra Candra; Syarif Hidayatullah; Reko Adilani; Dian Safitri; Aura Diana Salsabilah (POLITEKNIK LP3I JAKARTA, 2024)
MSME actors on Bintan Island face various challenges that can hinder their business development, one of the main challenges is the low level of financial literacy among MSME actors. This research aims to create a healthier and more sustainable economic environment on Bintan Island. By facilitating MSME actors in adopting accounting practices that are in accordance with accounting standards through a template based on Ms. Excel. The research methods used are qualitative descriptive, participatory and content analysis approaches. Meanwhile, the data collection techniques used are surveys, interviews, observations and FGD. The results of this study show that after the implementation of the SAK EMKM template based on Ms. Excel, the majority of respondents felt ease in preparing their business financial statements. They also feel helped by the SAK EMKM format provided in a template that has been automatically designed using formulas. In addition, the level of satisfaction with the use of this template is also quite significant, because respondents are very confident that the resulting financial statements are not only accurate, but also meet the accounting standards required for financing applications to financial institutions. The resulting impact for the government is that most respondents who have not completed their taxation plan to fulfill their tax obligations.